Unlocking success: leveraging alumni records as a strategic business asset / Khairunisa Abdul Khalik - Abdul Khalik, Khairunisa (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
In today's highly competitive business landscape, companies are constantly seeking innovative ways to gain a competitive edge. One often overlooked and valuable resource that businesses can tap into is their alumni network. By strategically leveraging the data stored in alumni records, companies can not only strengthen their brand image but also forge meaningful connections and unlock new opportunities. In this article, we will explore the significance of alumni records as a strategic business asset and how companies can harness their potential for success.